2007
DOI: 10.1021/jf071687a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fatty Acyl Composition and Quantity of Triglycerides on Bioaccessibility of Dietary Carotenoids

Abstract: A carotenoid-rich salad meal with varying amounts and types of triglycerides (TG) was digested using simulated gastric and small intestinal conditions. Xanthophylls (lutein and zeaxanthin) and carotenes (alpha-carotene, beta-carotene, and lycopene) in chyme and micelle fraction were quantified to determine digestive stability and efficiency of micellarization (bioaccessibility). Micellarization of lutein (+zeaxanthin) exceeded that of alpha- and beta-carotenes, which was greater than that of lycopene for all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
177
4
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(203 citation statements)
references
References 91 publications
21
177
4
1
Order By: Relevance
“…Similarly, previous investigations of the efficiency of transfer of individual carotenoids from a food matrix to the aqueous or micellar fraction in response to in vitro digestion have shown that β-carotene is more readily micellarised than lycopene [29,30,35]. These findings therefore support the validity of in vitro models for comparisons of the relative bioavailability of different carotenes.…”
Section: In Vitro Releasesupporting
confidence: 77%
See 1 more Smart Citation
“…Similarly, previous investigations of the efficiency of transfer of individual carotenoids from a food matrix to the aqueous or micellar fraction in response to in vitro digestion have shown that β-carotene is more readily micellarised than lycopene [29,30,35]. These findings therefore support the validity of in vitro models for comparisons of the relative bioavailability of different carotenes.…”
Section: In Vitro Releasesupporting
confidence: 77%
“…It is possible that the differences in uptake is related to structural changes during the storage of the soup, e.g. hydrolytic products of dietary lipids may modify physicochemical characteristics of the micelles [35]. The relative hydrophobicity of β-carotene and lycopene, their location and chemical form in the plant matrices, and their transfer between oil droplets and micelles are important, β-carotene in carrots are associated with proteins [36] surrounded by a thick membranous sheet and lycopene is present in the tomato as crystalloids that develop within or along thylakoid bodies [37].…”
Section: Caco-2 Cell Uptakementioning
confidence: 99%
“…between -carotene and lutein has been found in several studies. 9,12) Although there are few reports on the bioaccessibility of -tocopherol, Borel et al have reported that its bioaccessibility was highly variable between foods. They have found that lettuce and banana had high bioaccessibility, whereas nuts had low bioaccessibility.…”
Section: Discussionmentioning
confidence: 99%
“…9,12) However, the effects of the fatty acyl moiety of fats and oils, unsaponifiable matter, and other lipid classes on the bioaccessibility of carotenoids of diverse structures and y To whom correspondence should be addressed. …”
mentioning
confidence: 99%
“…Impor- tantly, the aged animals on walnuts also showed reduced microglial activity in the hippocampus. In addition to PUFAs, walnuts also contain other bioactive constituents which have been shown to influence brain function, including vitamin E, melatonin, and antioxidant polyphenols such as ellagic acid (Venkatachalam and Sathe, 2006) that could act synergistically with the PUFAs to increase dietary polyphenolic absorption and uptake following consumption (Huo et al, 2007).…”
Section: Walnut and Fish Polyunsaturated Fatty Acidsmentioning
confidence: 99%